When good messages go wrong: Perspectives on COVID-19 vaccines and vaccine communication from generally vaccine accepting individuals in Canada - Gabriela Capurro; Jordan Tustin; Cindy G. Jardine; S. Michelle Driedger (Taylor & Francis Group, 2022)
Vaccines are one of the most important and successful public health interventions to reduce the spread of infectious diseases. However, unlike childhood diseases and routine vaccines, COVID-19 is a novel threat, and COVID-19 vaccines may elicit specific anxieties. Through focus groups, we examine the concerns and attitudes toward the COVID-19 vaccine expressed by individuals who accept routine vaccinations in Canada. We also conducted a pre-focus group survey to document participant attitudes towards vaccines in general. While most participants had received at least one dose of the COVID-19 vaccine or had the intention to get it, many had concerns. First, participants felt anxious about the quick development and approval of the vaccines, even if they recognized that the vaccines have undergone clinical trials. Second, participants felt confused about shifting public health guidelines regarding vaccine safety, changing the interval between doses, and mixing different vaccine brands. Finally, participants said they felt abandoned when deciding whether to get vaccinated or not. People who generally accept vaccines expressed concerns about COVID-19 vaccines, mostly related to the inevitable uncertainties of a new vaccine (i.e. novelty, safety, mandates, etc.). COVID-19 vaccine hesitancy, understood as concerns about the novelty of a vaccine and the rapid implementation of it, could be useful for understanding questioning attitudes towards COVID-19 vaccines from people who accept routine vaccinations. Understanding COVID-19 vaccine hesitancy can also provide valuable insights as booster doses are periodically needed and people may not be as accepting of these additional doses.